Individual identification using the RapidHIT™ ID system for forensic samples. (November 2020) - Murakami, Chikako; Irie, Wataru; Sasaki, Chizuko; Nakamaru, Naomi; Sakamoto, Momoko; Nagato, Junpei; Satoh, Fumiko
Highlights: Enables identification of postmortem bodies at different stages of decomposition. Optimization of RapidHIT ID ACE GFE and RapidINTEL with minute samples. Demonstrated reproducibility from samples after various storage conditions. Abstract: The RapidHIT™ ID system produces GlobalFiler™ analysis results after a short operating time. This device is effective because it automatically extracts DNA from oral mucosal cells or from blood stains and saliva collected at a crime scene, with subsequent polymerase chain reaction performed to produce a DNA profile. Two types of dedicated cartridges are available for RapidHIT™ ID: the RapidHIT™ ID ACE GlobalFiler Express sample cartridge for oral cells and other samples and the RapidINTEL™ sample cartridge for minute samples, such as blood stains. Previously validated specimens include oral mucosa cells and blood stains left at crime scenes. There have been no reports of blood and nail clipping samples collected from the postmortem bodies at the time of death. This report summarizes the results of using the RapidHIT™ ID system by collecting a variety of actual forensic samples from postmortem bodies at different stages of decomposition, which were subsequently analyzed using these cartridges.